Catalytic reforming of oxygenated hydrocarbons for the hydrogen production: An outlook - Mohammad Tazli, Azizan; Aqsha, Aqsha; Mariam, Ameen; Ain Syuhada, .; Klaus, Hellgardt; Sumaiya, Zainal Abidin; Sher, Farooq (Springer, 2023)
The catalytic steam reforming of oxygenated hydrocarbons has been holding an interest in scientific societies for the past two decades. The hydrogen production from steam reforming of glycerol, ethanol and other oxygenates such as ethylene glycol and propylene glycol are more suitable choice not just because it can be produced from renewable sources, but it also helps to decrease the transportation fuel price and making it more competitive. In addition, hydrogen itself is a green fuel for the transportation sector. The studies on the production of hydrogen from various reforming technologies revealed a remarkable impact on the environmental and socio-economic issues. Researchers became more focused on glycerol steam reforming (GSR), ethanol steam reforming (ESR) and other oxygenates to investigate the catalyst suitability, their kinetics and challenges for the sustainability of the oil and gas production. In the present work, the authors critically addressed the challenges and strategies for hydrogen production via GSR, ESR and other oxygenates reforming process. This review covers extensively thermodynamic parametric analysis, catalysts developments, kinetics and advancement in the operational process for glycerol, ethanol and few other oxygenates. This detailed investigation only highlights the steam reforming process (SRP) of these oxygenates at the laboratory experimental stage. It was found that from this review, there are many technical issues, which lead to economic challenges. The issues are yet to be addressed and thus, these particular applications require faster accelerations at the pilot scale, taking into the consideration of the current pandemic and economic issues, for a safer and greener environment.